The potential of polymeric micelles in the context of glioblastoma therapy - Morshed, Ramin; Cheng, Yu; Auffinger, Brenda; Wegscheid, Michelle; Lesniak, Maciej S. (Frontiers in Pharmacology, 2013)
Glioblastoma multiforme (GBM), a type of malignant glioma, is the most common form of brain cancer found in adults. The current standard of care for GBM involves adjuvant temozolomide-based chemotherapy in conjunction with radiotherapy, yet patients still suffer from poor outcomes with a median survival of 14.6 months. Many novel therapeutic agents that are toxic to GBM cells in vitro cannot sufficiently accumulate at the site of an intracranial tumor after systemic administration. Thus, new delivery strategies must be developed to allow for adequate intratumoral accumulation of such therapeutic agents. Polymeric micelles offer the potential to improve delivery to brain tumors as they have demonstrated the capacity to be effective carriers of chemotherapy drugs, genes, and proteins in various preclinical GBM studies. In addition to this, targeting moieties and trigger-dependent release mechanisms incorporated into the design of these particles can promote more specific delivery of a therapeutic agent to a tumor site. Despite these advantages however, there are currently no micelle formulations targeting brain cancer in clinical trials. Here, we highlight key aspects of the design of polymeric micelles as therapeutic delivery systems with a review of their clinical applications in several non-brain tumor cancer types. We also discuss their potential to serve as nanocarriers targeting GBM, the major barriers preventing their clinical implementation in this disease context, as well as current approaches to overcome these limitations.